Scutellarin prevents obesity-induced renal fibrosis via reduced activation of AP-1 - Haoan Yi; Yibing Jiang; Wei Li; Ling Shen; Wei Zhang; Shude Li; Yushan Xu; Fei Li (Journal of Translational Medicine)
Abstract Background Renal fibrosis is characterized by the formation of scar tissue in the kidney parenchyma. Obesity, with its rising global incidence, has become a significant cause of renal fibrosis. This study investigates the effect of Scutellarin (SCU) on obesity-induced renal fibrosis. Methods Rats were fed a high-fat and high-sugar diet (HFSD) for 40 weeks. SCU was administered orally at doses of 25, 50, and 100 mg/kg/day during the last 8 weeks. Metabolic function was assessed by measuring serum triglycerides (TG), total cholesterol (TC), and glucose levels. Renal function was evaluated by analyzing serum uric acid (UA), creatinine (CRE), and blood urea nitrogen (BUN). RNA-seq was used to evaluate transcriptome changes in the kidney. Histopathological changes were examined using HE and Masson staining. Protein expressions and localization of FOS, JUN, FN, and TGF-β1 were analyzed by western blot, immunohistochemistry, and immunofluorescence. Results HFSD-fed rats exhibited significant increases in body weight, serum TG, TC, and glucose levels, alongside elevated UA, CRE, and BUN levels, indicating metabolic and renal dysfunction. SCU treatment significantly improved these metabolic and renal parameters across all doses. Biochemical analyses and RNA-seq results confirmed the absence of dose-dependency in the effects of SCU. Histopathological analysis showed a reduction in glomerular hypertrophy and collagen deposition in the SCU-treated groups. RNA-seq data indicated a downregulation of Activator Protein 1 (AP-1), composed of FOS and JUN, at the transcriptional level. Western blot analysis confirmed that SCU treatment reduced both the expression and phosphorylation levels of FOS and JUN. Additionally, SCU downregulated the expression of fibrosis-related proteins TGF-β1 and FN, contributing to a reduction in renal fibrosis. Conclusion SCU alleviates obesity-induced renal fibrosis through the downregulation of AP-1 activity and the expression level of fibrosis-related proteins TGF-β1 and FN.